A New Fossil Snake-Fly Species from Baltic Amber (Raphidioptera: Inocelliidae). (1995) - Engel, Michael S.
Abstract : A new species of inocelliid snake-fly, Fibla carpenteri, is described and figured frorn Middle to Upper Eocene Baltic amber. The species belongs to the nominate subgenus and is the largest amber snake-fly currently known. The aberrant fossil species Inocellia peculiaris is transferred to a new genus, EIectrinocellia, and placed in a new subfamily, the Electrinocelliinae, sister to the remainder of the Inocelliidae.